Evaluating the Role of the Regional People’s Representative Council (DPR) Secretariat in Supporting the Administration of Legislative Function: A Public Policy Implementation Perspective in East Java Province - Slamet Abidin; Widyawati Widyawati; Kristyan Dwijosusilo (International Journal of Social Science and Humanity, 2026)
The Secretariat of the Regional People’s Representative Council (DPRD) is an inseparable component of the structure of regional government, both at the provincial and the regency/city level, and is closely related to the performance of the DPRD. Nevertheless, many parties still do not fully understand the role and function of the DPRD Secretariat in its daily activities. This study evaluates the role of the East Java Provincial DPRD Secretariat in supporting the administration of the DPRD functions through the lens of public policy implementation theory. A qualitative descriptive approach was employed, with the research conducted at the Office of the East Java Provincial DPRD Secretariat. Informants comprised DPRD members, officials, and staff within the East Java Provincial DPRD environment, consisting of four key informants and six main informants. Data were gathered through documentation and in-depth interviews and analyzed using triangulation by matching interview data, observations, and supporting documents. The findings indicate that, in implementing the representative function of the Provincial DPRD, the role of the Secretariat—particularly the staff—remains largely confined to facilitating completeness requirements that support the three functions of the DPRD: legislation, budgeting, and oversight. The DPRD Secretary, drawn from the civil-service (PNS) corps and tasked with serving the Council, has performed a meaningful role that is, however, not yet fully optimal. Although the staff role is essentially facilitative, performance improvement is required to prepare the needs of DPRD members more carefully, especially in support of the legislative function. Viewed against implementation theory, the constraints observed—weak inter-agency coordination, insufficient human resources, excessive specialization, and unclear procedures—correspond to deficiencies in communication, resources, and bureaucratic structure. It is recommended that staff participate more frequently in education and training programs to strengthen competence.